THE IMPORTANCE AND THE ROLE OF TOURISM IN THE ECONOMIC AND SOCIAL LIFE OF ALBA COUNTY - MOISĂ, Claudia Olimpia (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 17 (2015): Annales Universitatis Apulensis Series Oeconomica, 2015)
With an extremely varied natural landscape and an attractive and complex anthropic tourism potential, Alba County is unfortunately below the national average in terms of heritage tourism leverage but, through the stakeholders involvement, with big prospects of development in terms of tourism. The objective of this paper is to highlight the role played by the tourism activity in the economy of Alba County. For this purpose, a thorough analysis was done regarding what tourism means and which are the factors that influence it, it was stressed the role and both the economic and social importance at the county Alba and were identified the main opportunities for its development.